Perceived Influence of Instructional Delivery, Classroom Management Training, and Mentoring on Pre-Service Teachers’ Professional Preparedness - Ferdinand H. Magpayo (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
Teachers’ influence on students is inevitable and enduring. Preservice teachers look up to their teachers as models and coaches at the same time. More often, PSTs’ work ethic, styles, and even behaviors are largely influenced by teachers, and they extend them until their first venture into teaching. This study focuses on the factors that contribute to the professional readiness of pre-service teachers, particularly instructional delivery, mentoring, and classroom management preparation. Conducted among fourth-year Bachelor of Secondary Education students at Bulacan State University College of Professional Teacher Education, the research employed a quantitative descriptive-comparative approach using survey questionnaires. The investigation was grounded on the idea that teacher education programs significantly shape the competence and preparedness of future educators, although limited studies have examined these factors within the context of the institution. Descriptive statistics were used to summarize and interpret the data, while inferential statistics were used to determine differences in perceived professional preparedness according to gender and teaching specialization. Findings revealed that instructional delivery had a very high level of influence, while classroom management training and mentoring showed high levels of influence on professional preparedness. Overall, pre-service teachers reported a high level of professional preparedness. No significant differences were found when respondents were grouped according to gender and teaching specialization. The findings highlight the importance of strengthening classroom management training, mentoring feedback, and opportunities for pre-service teachers to develop strategies for handling diverse classroom situations.